Postoperative Early Outcomes of Conventional versus Minimally Invasive Multivessel Coronary Artery Bypass Surgery: Retrospective Study - Elif Erdogan; Gokhan Gokarslan; Feragat Uygur; Murat Yardımcı; Erkan Kaya; Damla Sariguney (Ukrainian Journal of Cardiovascular Surgery, 2021)
Minimally invasive coronary artery bypass grafting (CABG) is a new technique developed in recent years apart from the conventional method. Our first objective is to compare the postoperative early outcomes of conventional and minimally invasive multivessel (MIM) CABG methods, and second objective is to compare perioperative differences between two surgical techniques. This retrospective, comparative study was conducted at a university hospital with 100 patients, who underwent CABG surgery from November, 1 2019 to June, 1 2020. The data of 50 patients, who underwent MIM CABG (Group M), was certain. Among the patients operated with the conventional method (Group C), 50 patients were randomly selected from the same time period. Examination of early postoperative outcomes revealed that Group C had significantly higher intensive care unit (ICU) stay (p=0.013), significantly higher mechanical ventilation time in ICU (p<0.001), and significantly higher isolated systolic blood pressure (p=0.013). Examination of perioperative variables revealed that Group C had significantly shorter duration of surgery (p<0.001), significantly shorter aortic cross-clamp time (p<0.001), significantly shorter cardiopulmonary bypass (CPB) time (p<0.001), significantly lesser graft numbers (p<0.001), significantly lesser left internal mammary artery use (p<0.05), and significantly lesser inotropic support after CPB was discontinued (p<0.05). In the light of these results, MIM CABG was associated with enhanced postoperative early outcomes with prolonged surgery time compared to conventional method.